Study on physiological characteristics of fruit cracking of different jujube varieties - LIU Wei; WANG Jianyu; WANG Zhenlei; LIN Minjuan (Guoshu xuebao)
[Objective] Jujube (Ziziphus jujuba Mill.) is native to China with good tolerance to abiotic stresses. Jujube fruit is rich in nutrients and is edible and medicinal. Fruit cracking is a limiting factor influencing production of jujube. The cell wall materials, cell wall degrading enzymes, and peel structure are closely related to the occurrence of fruit cracking. The purpose of this experiment was to explore the changes in fruit water-immersion cracking rate, cell wall substances and cell wall degrading enzymes in different period of fruit development of the varieties with different potential of fruit cracking in order to provide scientific basis for the prevention and control of cracking of jujube fruits. [Methods] The fruits of Fucuim (easy cracking) and Dalizhizao (anti-cracking) were used as materials collected from the Jujube Germplasm Resource Nursery of the Horticultural Experiment Station of Tarim University. The experiment design was single-plant plot with three replications.80 fruits from each plant were sampled in four periods of pre-white ripening, white ripening, half-red stage and full-red stage, and kept in an ice box to bring back to the laboratory for separation of the pulp and pericarp, and then treated with liquid nitrogen and put into -80 ℃ ultra-low-temperature refrigerator for storage. The observations were made to analyze the rate of fruit cracking by immersion, pericarp cell wall composition (cellulose, hemicellulose, water-soluble pectin, ion-bound pectin and covalently bound pectin) and the activities of related degrading enzymes (polygalacturonase, cellulase, catalase, superoxide dismutase). [Results] The pericarp strength was positively correlated with the content of cell wall components and negatively correlated with fruit cracking rate. Prior to fruit maturity, the water-soluble pectin, covalently bound pectin, and ion-bound pectin content decreased in the pericarp of the anti-cracking and easy cracking varieties, the ion-bound pectin, covalently bound pectin content, and cellulose content decreased in the pulp of anti-cracking variety, and the ion-bound pectin and covalently bound pectin content increased in the pulp of easy cracking variety. Prior to fruit maturity, both the anti-cracking and the easy cracking varieties showed an increase in the hemicellulose content in the pericarp and pulp, an increase in the soluble pectin content in the pulp, and a decrease in the cellulose content in the pulp of jujube fruit. The covalently bound pectin and hemicellulose were higher in the pericarp of anti-cracking variety than those of c the easy cracking variety. The vater-soluble pectin, ion-bound pectin, covalently bound pectin, and cellulose content in the pericarp were not correlated with the rate of fruit cracking, while the water-soluble pectin content and the rate of fruit cracking in the pulp showed a highly significant positive correlation, and cellulose content showed a highly significant negative correlation with the rate of fruit cracking. The pericarp of easy cracking variety contained less water-soluble pectin, hemicellulose, and more ionbound pectin and covalently bound pectin. The pectinase and cellulase activities in the pericarp affect the occurrence of cracking, and in the semi-red fruit stage, the pericarp polygalacturonase (PG) and cellulase activities of the anti-cracking variety was higher than those of the anti-cracking variety. The polyphenol oxidase (PPO) activity in the pericarp of anti-cracking variety was significantly greater than that of easy cracking variety, and there was a highly significant positive correlation between the PPO activity in the pulp and the rate of fruit cracking. The activities of the superoxide dismutase (SOD), Catalase (CAT), PPO, Cellulase (CE) and PG in the pericarp were not correlated with the rate of fruit cracking. The pericarp CAT activity of the anti-cracking variety in the semi-red stage of fruiting was highly significant greater than that of the anti-cracking variety, the activity of the SOD was highly and significantly less than that of the anti-cracking variety, and the decrease in the pericarp PG activity of the anti-cracking variety was greater than that of the easy cracking variety. The decrease of the PG activity in the pericarp of the anti-cracking variety was greater than that of the easy cracking variety. The PG activity and CAT activity in the pulp of the anti-cracking variety were significantly or highly and significantly higher than those of the easy cracking variety, and the cellulase activity was higher than those of the easy cracking variety. The PPO activity of the anti-cracking variety was significantly lower than those of the easy cracking variety, and the SOD activity was lower than those of the easy cracking variety. [Conclusion] The fruits of jujube in the brittle ripening stage were sensitive to water, and the earlier the appearance of cracked fruits under water-soaked conditions, the higher the rate of cracking of variety. During the sensitive period of fruit cracking (in semi-red stage), Dalizhizao showed higher content of the covalently bound pectin and hemicellulose in the pericarp, and higher content of the ion-bound pectin, covalently bound pectin and cellulose in the pulp. The variety with high PG, cellulase and CAT activities in the pericarp and pulp was more resistant to cracking, and the lower the PG and cellulase activities in the pericarp and pulp, the higher the PPO and CAT activities, the greater the resistance to cracking.